KEBIJAKAN INDONESIA TERHADAP PENGUNGSI ROHINGYA DI NANGROE ACEH DARUSSALAM - Wulanndari Trikusumaningsih (HI 15 UMY 464, 2015)
*464 Refugee is one of the important issues in the world of international relations recently. The outbreak of conflict in various countries make many of refugees were trying to obtain asylum to sustain their life. Indonesian accepts Rohingya refugees who stranded in Indonesian waters in May 2015. The decision to accept Rohingya Refugees in Indonesia was announced after the tripartite meeting that held by Indonesia, Myanmar and Thailand in Pataraja, Malaysia. This issue is interesting to discuss because there is a change is Indonesian policy that is used to expel the Rohingya refugees and now even accepted. The aim of this paper is to explain the reasons why Indonesia accepts Rohingya refugees in Nangroe Aceh Darussalam. This study uses qualitative analysis, which the authors tried to describe and explain the reason why Indonesia accepts Rohingya refugees in Nangroe Aceh Darussalam. The data that authors use comes from books, journals, documents, and materials from the internet. In this study, the author describe Aceh as a region that use Islamic law as their identity and uphold rights of humanity which are become the reason why the accepted the Rohingya refugees. Furthermore, Indonesia gets pressure from internal and external parties to accept Rohingya refugees. This study shown that the acceptance of Rohingya refugees in Nangroe Aceh Darussalam is the result of the identity that exists in Aceh and the pressure conducted by a network of institutions in the country and abroad.